ChemInform Abstract: Synthesis and Cytotoxicity of New Quinoline Derivatives. Issue 4 (31st January 2013) - Meshram, H. M.; Reddy, B. Chennakesava; Kumar, D. Aravind; Kalyan, M.; Ramesh, P.; Kavitha, P.; Rao, J. Venkateswara
Abstract The title compounds are obtained from 4‐haloquinoline (I) following the Suzuki protocol.